Impact of precise land levelling on pearl millet-based cropping systems - Singh, Y P; Tomar, Sandeep S; Yadav, Ravi; Gurjar, Ravi; Sharma, Deependra (Indian Farming, 2022)
The crop production under traditionally levelled fields is declining system productivity, profitability and water productivity over time. In these conditions, precise laser land levelling reformed soil properties and improved system productivity, economic profitabilityand water productivity of the pearl millet-based cropping system. The yield of crops, pearl millet equivalent yield, net returns and water productivity with precise land levelling were enhanced as compared with the traditional land levelling method. Like-wise,pearl millet equivalent yield, net returns and total water use were greater with pearl millet-wheat followed by pearl millet-mustard and lowest with pearl milletchickpea under the study.